Early Assessment of Response to Radiofrequency Ablation With CT Perfusion Imaging in Rabbit VX2 Liver Tumor Model - Yue, Xiaofei; Dong, Xiangjun; Huang, Mengting; Yang, Hongli; Qian, Kun; Yi, Changhong; Alwalid, Osamah; Ren, Yanqiao; Han, Ping; Li, Qian (Frontiers in Oncology, 2021)
Objectives: To evaluate the diagnostic of CT perfusion and assess characteristics of quantitative parameters for discriminating viable tumors from benign periablational enhancement (BPE) after radiofrequency ablation (RFA) in the rabbit liver VX2 tumor model with pathological results as the standard. Methods: Twenty-eight VX2 liver tumors were treated with RFA, on days 1, 3, 7, and 14, seven rabbits were randomly chosen for CT perfusion and performed pathology examinations immediately. The perfusion parameters were observed in both BPE and viable tumors, including blood flow (BF), blood volume (BV), time to peak (TTP), permeability (P), arterial liver perfusion (ALP), portal venous perfusion (PVP) and hepatic perfusion index (HPI), along with the proﬁle of time-density curves (TDCs) and pseudo-color images of the parameters, then compared with the pathology results. Results: A total of 26/28 rabbits successfully underwent CT perfusion, while 6/26 lesions were confirmed to be viable tumors. The TDCs of BPE were mainly speed-up platform curves (15/26), while the viable tumors showed mainly speed-up speed-down (3/6) and speed-up platform (2/6) curves. The PVP values were significantly higher, and the HPI values were significantly lower for BPE at all time points than viable tumors (P < 0.01). These characteristics of CT perfusion parameters were consistent with pathological changes. Conclusions: The TDCs, PVP and HPI have the potential to indicate BPE and viable tumors effectively early after RFA treatment, the results were highly consistent with pathology. CT perfusion has advantages with great efficacy in monitoring the therapeutic effect early after RFA treatment.